2020
DOI: 10.14426/cristal.v8i2.250
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualising (dis)advantage in South African higher education: A capability approach perspective

Abstract: Higher education policy in South Africa uses the concept of ‘historically disadvantaged’ to address inequities and inequalities. Disadvantage specifically refers to black students who are marginalised in higher education due to structural factors associated with the apartheid legacy of segregation. In this paper, drawing from the capability approach, the authors argue that (dis)advantage can be better understood in terms of students’ capabilities, functionings, and agency, which go beyond race to address other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…In short, the teaching and learning aids brought about multiliteracy development in that learners were able to name the days of the week in both English and Tonga. These findings are confirmed by Ngcobo et al (2016), who claimed that translanguaging as a method of teaching and learning promises to promote literacy among students in both their native African languages and English. Additionally, according to Banda (2018), a black township school in Cape Town uses translanguaging and English African mother tongues as linguistic adaptations for teaching and learning.…”
Section: Prospects Of Translanguaging In Multilingual Classroomssupporting
confidence: 54%
See 1 more Smart Citation
“…In short, the teaching and learning aids brought about multiliteracy development in that learners were able to name the days of the week in both English and Tonga. These findings are confirmed by Ngcobo et al (2016), who claimed that translanguaging as a method of teaching and learning promises to promote literacy among students in both their native African languages and English. Additionally, according to Banda (2018), a black township school in Cape Town uses translanguaging and English African mother tongues as linguistic adaptations for teaching and learning.…”
Section: Prospects Of Translanguaging In Multilingual Classroomssupporting
confidence: 54%
“…Other scholars (Daka et al, 2020;Kafusha et al, 2021;Mumba & Mkandawire, 2019) stated that translation is a cognitive process that occurs spontaneously and cannot be halted in a bilingual or multilingual individual because it seems to be normal to rely on translation when confronted with foreign words and/or expressions. In addition, Ngcobo et al (2016) claimed that translanguaging as a method of teaching and learning promises to promote literacy among students in both their native African languages and English. Additionally, Banda (2018) indicated that a black township school in Cape Town uses translanguaging and English African mother tongues as linguistic adaptations for teaching and learning.…”
Section: Introductionmentioning
confidence: 99%
“…It is vital for the South African higher education system to grapple with the real challenges poor students are facing. As Gore and Walker (2020) feel that the use of vaguely defined and limited terminology such as "disadvantage" in South African higher education, the policy lacks clarity and focus. Studies such as Walker et al (2009); Spaull (2013); and Van der Berg (2018) may provide a deeper understanding of the multiple dimensions in which students are deprived in South African universities.…”
Section: Background Of the Studymentioning
confidence: 99%
“…Firstly, the legacy of apartheid and colonialism is still causing marginalized communities to have limited access to adequate social determinants of health, which in turn cause further disempowerment by the limited choices available for sustaining health and well-being [4]. Secondly, many health care students come from marginalized, under-resourced communities resulting in inadequate preparation of these students for tertiary studies [5]. Thirdly, the quadruple burden of disease in uences health of South Africans, including, challenges in maternal, new-born and child health; HIV/AIDS and tuberculosis (TB); non-communicable diseases; violence and injury [6].…”
mentioning
confidence: 99%